Thermal and Spectral Sensitivities of Discrete Slow Potentials in Limulus Eye - Adolph, Alan R. (The Rockefeller University Press, 1968)
The discrete, subthreshold, slow potential fluctuations (SPF's) which can be recorded intracellularly in Limulus ommatidia are sensitive to temperature and light wavelength. SPF frequency increases with increasing temperature (Q (10) about 3.5) and light intensity. The effects are additive. SPF rise and decay time decrease with increasing temperature (Q (10) between 2 and 3). There is a peak, near 520 nm, in the spectral sensitivity of SPF frequency. This peak may correspond to the wavelength of maximum absorption by rhodopsin in the ommatidia. Hydroxylamine produces a rapid, irreversible reduction of SPF frequency and amplitude perhaps owing to its action on the photopigment. The cornea and crystalline cones fluoresce (peak about 445 nm) when excited by near-ultraviolet energy (380 nm peak) and this fluorescence may influence SPF spectral sensitivity measurements. These findings suggest that the SPF's are the results of photolytic and thermolytic reactions occurring in the ommatidial visual pigments and that they have a role in the mechanisms which transduce light to electrical activity in the visual receptors.